International Students and “The Presentation of Self” Across Cultures - Kamara, Abu (Journal of International Students, 2017)
Findings from this qualitative research study suggest that some international students view social and academic interactions not simply as mediums for absorbing requisite sociocultural and academic norms, and discipline knowledge, but also as stages for expressing their varied identities. As a result, whenever students’ ability to present their preferred identity is threatened, whether due to language competency issues or discrimination, some attempt to regain their equilibrium by withdrawing from social and academic interactions. However, the findings also suggest that, in some instances, students who find their ideas marooned in the space between silence and language rediscover the ability for expression in the language of space and time, and comparison and contrast.